SUPERVISI KEPALA MADRASAH DALAM PROSES PEMBELAJARAN DARING DI MAN 1 MODEL LUBUKLINGGAU - ekalia, juwita (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to find out objectively about the supervision of the head of madrasah, especially academic supervision of the online learning process at MAN 1 Model Lubuklinggau regarding academic supervision planning, supervision implementation academic and follow-up academic supervision caused by changes in system processes face-to-face learning becomes online learning. As for the research approach used is a qualitative descriptive research case study type. Data sources are the head of the madrasa, became a source of informants who were supported by other sources, namely teachers, and education staff at MAN 1 Model Lubuklinggau. While the data collection techniques through in-depth interviews, observation documentation. Data analysis techniques through examples interactive based on Miles Huberman. The results showed that: 1) Supervision planning carried out by the head of the madrasah at MAN 1 Model Lubuklinggau has been carried out including the stages of compiling a supervision team, formulating supervision objectives, setting goals, making schedules and studying supervision instruments. 2) Implementation of supervision is carried out with an initial meeting of activities through virtual class visits and observations using a collaborative approach. 3) The results of supervision by use results of planning, implementation and assessment of learning 4) Follow-up, from the implementation of supervision by analyzing the results of supervision, evaluating and guiding teachers, holding meetings, group discussions and holding workshops